Exploring sports fans aggression between contact and non-contact sports among students Faculty of Sport Science and Recreation / Siti Radhiah Arshad - Arshad, Siti Radhiah (2015)
This study was conducted to identify fans aggressions between contact and non-contact sport fans. The purposes of this study were (1 ) to determine the influences of socio demographic variables between the both participants (respondents). Besides that, (2) to investigates the influences of level of competition towards fans aggressions and this research also (3) to examine the influences of contact or non contact sport toward fans level aggression This study was conducted among 254 respondents who are students from FSR UiTM Negeri Sembilan Campus Seremban. The respondents were selected using the satrified random sampling technique. The study found the only socio-demographic variables of: (1) age; (2) gender; (3) level of education; and (4) highest level of competition, using descriptive statistic. The study also highlighted two section included, first to measure the level of competition toward the level of fans frustration, using ANOVA statistic and second is, to measure the attitude toward aggression between contact and non-contact sport fans using independent t-test.